2021
DOI: 10.36076/ppj.2021/24/e269
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupuncture and Physiotherapy on Patients with Knee Osteoarthritis: A Randomized Controlled Study

Abstract: Background: Osteoarthritis is the most prevalent form of joint disease, and the most common location is the knee. Objectives: The aim of this study was to determine the effect of acupuncture treatment and physiotherapy on pain, physical function, and quality of life (QOL) in patients with knee osteoarthritis (KOA). Study Design: This study was a prospective, randomized, controlled clinical trial. Settings: The research took place in the interventional pain unit of a tertiary center in a university hospital. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…For diseases such as tendinopathy (PHT), ESWT can signi cantly reduce pain by acting on soft tissues to improve function [31][32][33]. In addition to ESWT treatment, in some studies of maneuver, acupuncture and physiotherapy, they have reported that the therapeutic target within the soft tissue can still relieve pain and improve patient function in KOA patients by releasing and stimulating therapeutic targets inside soft tissues [34][35][36][37]. Therefore, the soft tissue is an important target for the treatment of disease using ESWT.…”
Section: Discussionmentioning
confidence: 99%
“…For diseases such as tendinopathy (PHT), ESWT can signi cantly reduce pain by acting on soft tissues to improve function [31][32][33]. In addition to ESWT treatment, in some studies of maneuver, acupuncture and physiotherapy, they have reported that the therapeutic target within the soft tissue can still relieve pain and improve patient function in KOA patients by releasing and stimulating therapeutic targets inside soft tissues [34][35][36][37]. Therefore, the soft tissue is an important target for the treatment of disease using ESWT.…”
Section: Discussionmentioning
confidence: 99%
“…[29–31] In addition to ESWT treatment, in some studies of maneuver, acupuncture and physiotherapy, they have reported that the therapeutic target within the soft tissue can still relieve pain and improve patient function in KOA patients by releasing and stimulating therapeutic targets inside soft tissues. [32–35] Therefore, the soft tissue is an important target for the treatment of disease using ESWT.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] In addition to ESWT treatment, in some studies of maneuver, acupuncture and physiotherapy, they have reported that the therapeutic target within the soft tissue can still relieve pain and improve patient function in KOA patients by releasing and stimulating therapeutic targets inside soft tissues. [32][33][34][35] Therefore, the soft tissue is an important target for the treatment of disease using ESWT. We observed that ESWT significantly relieved symptoms and improved function in patients with KOA; that the abundance of soft tissue around the knee joint was positively correlated with the treatment effect in patients with KOA.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the score, the better the health status. The SF-36 has high reliability and validity in the Chinese population 53 59 60…”
Section: Methods and Analysismentioning
confidence: 99%